Sedentary Behavior and Physical Function Decline in Older Women: Findings from the Women's Health Initiative. (21st May 2012) - Seguin, Rebecca; LaMonte, Michael; Tinker, Lesley; Liu, Jingmin; Woods, Nancy; Michael, Yvonne L.; Bushnell, Cheryl; LaCroix, Andrea Z.
Abstract : Sedentary behavior is associated with deleterious health outcomes. This study evaluated the association between sedentary time and physical function among postmenopausal women in the Women's Health Initiative Observational Study. Data for this prospective cohort study were collected between 1993–1998 (enrollment) and 2009, with an average of 12.3 follow-up years. Analyses included 61, 609 women (aged 50–79 years at baseline). Sedentary time was estimated by questionnaire; physical function was measured using the RAND SF-36 physical function scale. Mixed-model analysis of repeated measures was used to estimate the relationship of sedentary time exposures and changes in physical function adjusting for relevant covariates. Compared to women reporting sedentary time of ≤6 hours/day, those with greater amounts of sedentary time (>6–8 hours/day, >8–11 hours/day, >11 hours/day) reported lower physical function between baseline and follow up (coefficient = −0.78, CI = −0.98, −0.57, −1.48, CI = −1.71, −1.25, −3.13, and CI = −3.36, −2.89, respectively P < 0.001 ). Sedentary time was strongly associated with diminished physical function and most pronounced among older women and those reporting the greatest sedentary time. Maintaining physical function with age may be improved by pairing messages to limit sedentary activities with those promoting recommended levels of physical activity.